EKSPERIMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) BERBANTUAN INTERNET TERHADAP PRESTASI BELAJAR EKONOMI SISWA DITINJAU DARI MOTIVASI BELAJAR SISWA MA BANY KHOZIN JEMBER TAHUN AJARAN 2013-2014 - Rahman, Tri Malikul; Martono, Trisno; Murtini, Wiedy (Jurnal Pendidikan Insan Mandiri, 2015)
The purpose of this study are: (1) to determine differences in the effect of the Problem Based Learning Model-aided internet on economic achievement (2) to determine differences in the effect of high motivation, middle motivation and low motivation on economic achievement (3) to determine interaction effects of motivation and models of instruction on learning and economic achievement. The population were students MA Bany Khozin Jember. Sampling by simple random sampling technique. The study sample consisted of  72 students.Based on the results of data analysis, it was concluded that: (1) There are significant differences model of problem-based learning and internet-assisted learning varied lectures on learning achievement of economic, in terms of motivation to learn in MA Bany Khozin Jember is based on the significant value of 0.041 learning model <0.05. (2) There are significant differences learning motivation high and low learning motivation toward achievement of economic study in MA Bany Khozin Jember based on a calculation that is based on the motivation to learn the significance of 0.034 <0.05. (3) There is interaction effect between the use of PBL learning model and conventional with students' motivation on student achievement MA Economics subjects Bany Khozin Jember is based on the significant value of 0.45 <0.05.Keywords: Problem Based Learning, internet, motivation and achievement